In vivo exposure for fear of pain and avoidance of movement in low back pain - Érica Brandão de Moraes; Francisco Farias Martins Júnior; Cibele Andrucioli de Mattos-Pimenta
ABSTRACT Objectives: to verify the effects of hierarchization and in vivo exposure for fear of pain, avoidance of movement, and anxiety in chronic low back pain. Methods: quasi-experimental study. The 27 patients who participated graded the damage associated with the movements in each of the 40 activities of daily living depicted in pictures using a scale from 0 to 100. The patients chose five out of all the activities that received a score higher than 50 to carry out the exposure. The intensities of fear and anxiety were measured before and after each exposure session. Results: the frequencies of the gender were equal, and the mean age was 44.9 years. The activities chosen more frequently for the exposure were shoveling (33.3%) and running (33.3%). There was reduction of fear and anxiety before and after exposure (p<0.001). Conclusions: hierarchization and in vivo exposure were effective in reducing fear and anxiety.